Comparison of Cow Milk Consumption and Processed Products by Mother with Regurgitation in Baby - Ilmiasih, Reni (University of Muhammadiyah Malang, 2020)
Introduction: Regurgitation is a common issue in infants under six months of age who are at risk of esophagitis with excessive frequency and volume. This problem is due, in part, to allergies in the whey protein content in Cow's milk. Objective: The purpose of this research was to examine the connection between Cow's milk consumption and processed products by mothers with regurgitation frequency in infants. Method: This form of study is cross-sectional, with 44 respondents using a purposeful sampling technic in mothers who have children under six months of age. Analysis of data using the Independent t-test test with a nominal scale of data. Result: Â The findings showed an average regurgitation frequency was 2.4 times, and the results of the study showed an association between Cow's milk intake and refined goods by mothers with regurgitation in infants under six months with a p-value:0.014. Discussion: Enhanced frequency of regurgitation in mothers who consume Cow's milk and processed foods because of the risk of childhood allergy to the quality of Cow's milk protein, and it is advised that parents be conscious of the frequency of regurgitation due to mother-eaten food.